Cypress Twig Gall Midge, Taxodiomyia cupressiananassa (Osten Sacken) (Insecta: Diptera: Cecidomyiidae) - Celina Gomez; Russell F. Mizell, III (EDIS, 2009)
EENY-430, a 3-page illustrated fact sheet by Celina Gomez and Russell F. Mizell III, is part of the Featured Creatures collection. It describes this pest of bald cypress and pond cypress — its distribution, description, life cycle and biology, hosts, damage, and management. Includes selected references. Published by the UF Department of Entomology and Nematology, February 2009.